Teacher's Work Culture to Realize High Quality of Islamic School (Site Study at MTs. Qodiriyah Harjowinangun Dempet Demak) - Suratno, Suratno (2011)
The objectives of this research are to describe (1) characteristic of Teacher's Work Relationship at MTs. Qodiriyah Harjowinangun Dempet Demak, (2) Characteristic of Social Relationship of teacher at MTs. Harjowinangun Dempet Demak. This research is qualitative research and uses ethnography design conducted at MTs. Qodiriyah Harjowinangun Dempet Kabupaten Demak. The data are information related to characteristic of teacher's work culture. Data sources of this research event, informant, and document. Technique of data collection are observation, in-depth interview, and documentation. Data are analyzed using Interactive Model begin with (1) reduction, (2) display, and (3) drawing conclusion. Validity is consisting of credibility, transferability, dependability, and conformability. The research's result shows that (1) work relationship at MTs. Qodiriyah Harjowinangun are not based on authority but relatedto He concept of mutual work mechanism. The teacher conducts the work relationship with the principal, school committee, teacher, school staff, parents, and community. Working relation is based on trust, respect, and recognition of competence and to build effective communication coupled with an effective critique. The working relationship is established within the scope of formal and non formal education, (2) The social relationship of teacher built on mutual respect, greet, familiarity, caring, solidarity, keep the feelings of others, and awareness of the importance of social relationships in building a conductive work of teachers cultur. The social relationship established in the scope of formal and non formal. Each month, teachers hold a social gathering with other Qodiriyah MA teachers everymont and in the event, teachers talk about the development of academic and non academic students.